Performance Analysis of Multilevel Inverter for Different Pulse with Modulation Techniques - kiran Y, Rishyendra; rao Jalri, Srinivasa (International Journal of Engineering and Technology, 2018)
This paper introduces Multi-level inverter with different Modulation Technique. Due to major advantages Cascaded H-Bridge Multi-level Inverter is presented in this paper.Â  Performance of Cascaded H-bridge Multi-level Inverter with Sinusoidal Pulse Width Modulated (SPWM) and Space Vector Pulse Width Modulated (SVPWM) has studied and compared their simulation results and FFT Analysis. Depending upon the carrier signals used in SPWM technique, it is sub divided into four types there are explained in this paper. The SVPWM technique used in this paper generate the switching signals directly from reference vector without using look up tables. The proposed SVPWM method can be used for any n-level inverter. Simulation results of 3-level and 5-level inverters with SPWM and SVPWM techniques are presented in this paperÂ Â